2015
DOI: 10.17925/enr.2014.09.02.113
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Apomorphine Therapy – How Does it Compare with Levodopa?

Abstract: Apomorphine administered subcutaneously has provided clinicians with an effective option for the rapid resolution of the symptoms of Parkinson's disease (PD) for over a quarter of a century. It is available for use either as an intermittent injection or a continuous infusion, depending on the severity of the patient's symptoms. This satellite symposium, held during the 18th International Congress of Parkinson's Disease and Movement Disorders in Stockholm, Sweden, from 8-12 June 2014, and chaired by Professor A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This resulted in a calculated mean time to full ON of approximately 24 minutes, but this is likely to be overinflated because some patients turned ON before 15 minutes and others before the 30‐minute time point. However, even calculating time to full ON in this way, the result is comparable to that seen with an injection of subcutaneous apomorphine in the APO202 and APO301 studies as well as the interim analysis from the AM‐IMPAKT study …”
Section: Discussionmentioning
confidence: 56%
“…This resulted in a calculated mean time to full ON of approximately 24 minutes, but this is likely to be overinflated because some patients turned ON before 15 minutes and others before the 30‐minute time point. However, even calculating time to full ON in this way, the result is comparable to that seen with an injection of subcutaneous apomorphine in the APO202 and APO301 studies as well as the interim analysis from the AM‐IMPAKT study …”
Section: Discussionmentioning
confidence: 56%
“…29 Interim results from the ongoing apokyn for motor improvement of morning akinesia trial study have shown that subcutaneous apomorphine injection produces a rapid and reliable TTO, with 95% of patients with morning akinesia achieving at least a 20-minute reduction in TTO and an average reduction of 40 minutes. 47,48 …”
Section: Suitable Candidates For Intermittent Apomorphine Injectionmentioning
confidence: 99%